IMMERSIVE TECHNOLOGY ADOPTION IN HEALTHCARE: READINESS, BARRIERS, AND PATIENT OUTCOMES - Taneja, Reetika; Dutta, Hitakshi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Purpose: The incorporation of Immersive Technologies, namely, AR (Augmented Reality), VR (Virtual Reality) and MR (Mixed Reality) is increasing rapidly across all the business sectors. Healthcare institutions are also integrating these technologies to strengthen clinical treatment, patient care, medical training and patient interaction. This study makes an effort to assess how healthcare institutions understand, adopt, and experience the integration of Immersive Technologies, more especially emphasizing on perceived value, implementation challenges and institutional readiness. Methodology: A quantitative as well as qualitative analysis of questionnaires, discussions and interrogations with doctors, hospital administrators, and technology staff employed at healthcare institutions that are using or exploring immersive technologies like VR, AR, and MR. The interviews and responses provided a report on the different methods by which these institutions implement technology, as well as the upsides and downsides they have witnessed. The responses were thoroughly reviewed to find prevalent themes and patterns. Findings: Immersive technology is an effective tool to enhance overall patient satisfaction and outcomes. The technology improves the treatment through personalized care and interactive visuals. Despite its numerous benefits, concerns about implementation costs, ethicality, time constraints, and the requirement for specialized training for the healthcare providers involved in the treatment procedure remains a significant challenge. Among 60 participants in this study, 41.7% identified that their institutions were sufficiently equipped to handle these technologies, while 33.3% disagreed and 25% were uncertain. 90% of the doctors had some awareness about immersive technologies in healthcare, with 41.7% confident and 48.3% having merely basic knowledge, and only 10% were entirely unaware. A significant number of doctors indicated time constraints (75% agreed, 11.7% strongly agreed) and cost (76.7% agreed, 16.7% strongly agreed) as significant barriers, while over 80% acknowledged ethical challenges. Furthermore, 80% of doctors believed immersive technologies could make healthcare more patient-centered and engaging, enhancing interactions between patients and providers, though 16.7% were uncertain and only a small fraction (3.3%) disagreed. Research Limitations: This study includes views from a few healthcare institutions, so the results may not be representative of all types of hospitals or clinics. Longitudinal studies on the changes in the patterns of adoption and challenges to implementation of immersive technology can be studied in future research. Practical Implications: The findings are relevant to healthcare service providers in terms of effective implementation of immersive technology. By addressing concerns related to cost, training, and ethical issues, healthcare institutions can improve their effectiveness of implementation and integrate immersive technologies to enhance patient care and treatment procedures. Originality: With emphasis on real word implications and institutional readiness, this study provides a distinctive institution-centered viewpoint on immersive technology in healthcare. It provides basis for further research and practical frameworks to harness immersive innovations in healthcare institutions.